2018
DOI: 10.3390/en11020394
|View full text |Cite
|
Sign up to set email alerts
|

Improving Vegetable Oil Properties by Transforming Fatty Acid Chain Length in Jatropha Oil and Coconut Oil Blends

Abstract: Efforts to improve the physical and chemical properties of vegetable oils as diesel fuels such as viscosity and calorific value are indispensable with the depletion of fossil oil reserves. Jatropha oil with long chain fatty acids and high degree of unsaturation is mixed with short chain saturated fatty acid coconut oil in various compositions. The mixture was heated and stirred for 30 min at 90 • C. This mixing leads to a decrease in viscosity which allows for the breaking of the bond. The fatty acid molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The free fatty acids in the distilled pyrolytic oil underwent transformation that changed the degree of unsaturation and the carbon chain's average length. The free fatty acid value was reduced from 5.6% (for pyrolytic oil) to 0.64% after the transesterification process, and this trend was also observed by Wahyudi et al [31]. This shows that fatty acid structure influences oil properties, and Kilonzi et al [32] observed that free fatty acids can lead to corrosion.…”
Section: Produced Biodiesel and Distilled Waste Tire Pyrolytic Oil Phsupporting
confidence: 68%
“…The free fatty acids in the distilled pyrolytic oil underwent transformation that changed the degree of unsaturation and the carbon chain's average length. The free fatty acid value was reduced from 5.6% (for pyrolytic oil) to 0.64% after the transesterification process, and this trend was also observed by Wahyudi et al [31]. This shows that fatty acid structure influences oil properties, and Kilonzi et al [32] observed that free fatty acids can lead to corrosion.…”
Section: Produced Biodiesel and Distilled Waste Tire Pyrolytic Oil Phsupporting
confidence: 68%
“…Nevertheless, it follows the order SOR < SON < SOJ, while values of AV and FFA are in the order SOR > SON > SOJ. The values of SG are related to their respective densities and SOJ having the highest of these values means it possess highest degree un-saturation of its fatty acid components (Wahyudi et al , 2018) and Adewuyi and Oderinde (2018) described such as a pointer to pi-electron system. This restricted pi-electron is shared with unoccupied d-orbital of iron and requires less energy for this bond to form complex with iron ions resulting in enhanced corrosion inhibition (Khanra et al , 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Present in FFA are the hydrophilic groups (carbonyl) which are double-bonded and hydroxyl groups as shown in Figure 2. Double-bonded groups as described by Wahyudi et al (2018) are more unstable and react easily due to high mobility of their electron. These bonds of fatty acids are important in that they tend to cause increase in surface chemistry toward interaction with metal vacant orbital and hydroxyl groups have been associated with corrosion inhibition capabilities (Marzorati et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Lv et al [35] observed that the CFPP of the biodiesel made from palm oil is 16 • C, which is relatively high in comparison with other biodiesels produced from edible vegetable oils, such as rapeseed oil and soybean oil, due to the lower unsaturated fatty acids of palm oil. Wardana et al [36] found that the CFPP increases with the increase of the amount of long carbon-chain fatty acids. In addition, the lower iodine values, which imply lower amounts of unsaturated fatty acids, corresponded to lower CFPP values for the biodiesel produced by adding 0.05 wt.…”
Section: Cold Filter Plugging Point Of the Biodieselmentioning
confidence: 98%